UPAYA PEMERINTAH DAERAH DALAM MENGEMBANGKAN USAHA PENGOLAHAN NENAS DI KECAMATAN TAMBANG KABUPATEN KAMPAR TAHUN 2016-2017 - Risna Yuli Busmelda; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study is entitled "The Efforts of Local Governments in Developing Pineapple Processing Enterprises in Tambang District of Kampar Regency year of 2016-2017". This study aims to determine the efforts of the Regional Government in developing pineapple processing businesses in the Tambang District of Kampar Regency and the inhibiting factors of the Regional Government's energy in developing the Pineapple Processing Business in the Tambang District of the Kampar Regency. The method used in this research is qualitative method. Data collection techniques used were interviews, observation and documentation. While the data used are primary data obtained from research locations in the form of research informants, which are then supported by secondary data in the form of document data.The results of this study indicate that the efforts of local governments in developing pineapple processing businesses in the Tambang District of Kampar Regency include coaching and development, product quality improvement, financing and cooperation. While the inhibiting factors of the local government in the effort to develop pineapple processing businesses in the Tambang District of Kampar Regency are budget constraints and unattractive packaging appearance.  Keywords: Local Government, pineapple processing, development.